The Nag Hammadi codices and their ancient readers: exploring textual materiality and reading practice - Linjamaa, Paul (2024)
Since their discovery in 1945, the Nag Hammadi Codices have generated scholarly debate as to their date and function. This study analyses the palaeography and codicology of the manuscripts, focusing on paratextual elements and scribal features. Linjamaa explores how Pachomian monks used the texts for spiritual development and pedagogical practices